2020
DOI: 10.1098/rstb.2019.0519
|View full text |Cite
|
Sign up to set email alerts
|

Drought and heatwave impacts on semi-arid ecosystems' carbon fluxes along a precipitation gradient

Abstract: The inter-annual variability (IAV) of the terrestrial carbon cycle is tightly linked to the variability of semi-arid ecosystems. Thus, it is of utmost importance to understand what the main meteorological drivers for the IAV of such ecosystems are, and how they respond to extreme events such as droughts and heatwaves. To shed light onto these questions, we analyse the IAV of carbon fluxes, its relation with meteorological variables, and the impact of compound drought and heatwave on the carbon cycle of two sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…However, ecosystem productivity in some regions affected by drought, especially parts of Scandinavia and Eastern Europe, appears to have been close to or even above average, as observed by eddy-flux towers, simulated by process-based vegetation models, and deduced from atmospheric CO 2 measurements and transport modelling in the so-called atmospheric inversion models [33,40,43,44]. In Southern Europe, net CO 2 uptake was generally above average, even though extreme summer temperatures were registered, as wetter than average conditions prevailed in summer 2018 [45]. The asymmetry in the responses of ecosystems to the extreme summer drought and heatwave is the most striking feature of the analyses presented in this issue, but this can be seen as the result of the variety and broad scope of the approaches.…”
Section: Ecological Perspectivementioning
confidence: 74%
See 3 more Smart Citations
“…However, ecosystem productivity in some regions affected by drought, especially parts of Scandinavia and Eastern Europe, appears to have been close to or even above average, as observed by eddy-flux towers, simulated by process-based vegetation models, and deduced from atmospheric CO 2 measurements and transport modelling in the so-called atmospheric inversion models [33,40,43,44]. In Southern Europe, net CO 2 uptake was generally above average, even though extreme summer temperatures were registered, as wetter than average conditions prevailed in summer 2018 [45]. The asymmetry in the responses of ecosystems to the extreme summer drought and heatwave is the most striking feature of the analyses presented in this issue, but this can be seen as the result of the variety and broad scope of the approaches.…”
Section: Ecological Perspectivementioning
confidence: 74%
“…Rödenbeck et al [40] find a larger role for temperature-correlated NEE anomalies than for those correlated with the SPEI06, and suggest an important contribution of TER in creating the Central European reduced net carbon uptake. Bastos et al [33], Smith et al [42], El-Madany et al [45] and Koebsch et al [53] report covariations of TER reductions with GPP reductions, as also observed during many previous droughts across the world. Atmospheric CO 2 observations suggest the balance of these reductions to have led to reduced net carbon uptake in many ecosystems (though see [38,[40][41][42], for some turning net sinks of carbon into sources).…”
Section: (A) Process Understandingmentioning
confidence: 82%
See 2 more Smart Citations
“…The rain mainly falls between October and April, with mean annual amounts of ca. 650 mm, with large interannual variations (El-Madany et al, 2020). The ecosystem is a typical Mediterranean semiarid tree-grass ecosystem (Dehesa) with low-density oak tree cover (Quercus Ilex (L.), 20 trees ha −1 ) (Bogdanovich et al, 2021).…”
Section: Study Sitementioning
confidence: 99%